Pengembangan Video Interaktif Praktikum Gerak Parabola untuk Meningkatkan Keterampilan Proses Sains Siswa - Izza Fauzia; Widiatmono, Restu (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2024)
This study aims to (1) develop an interactive video tutorial design for a parabolic motion practicum that is appropriate and feasible to enhance students’ science process skills; (2) evaluate the quality of the developed video in supporting the targeted skills; (3) examine the practicality of implementing the media in classroom settings; and (4) assess its effectiveness in improving students’ science process skills. The media development process was guided by instructional design principles, incorporating elements such as visual appeal, user interface, curricular alignment, science process skill integration, graphical representation, and overall pedagogical utility. Expert validation results indicated that the video tutorial possessed a very high level of quality in both content and presentation. Practicality was confirmed through positive feedback from students and favorable evaluations from physics teachers, highlighting the video’s usability and relevance in real classroom contexts. Furthermore, the effectiveness of the video was statistically validated using a Multivariate Analysis of Variance (MANOVA), yielding a significant p-value (p < 0.001), alongside a high N-Gain score of 0.91, suggesting a substantial improvement in students’ science process skills. These findings demonstrate that the developed interactive video is a valid, practical, and highly effective educational tool for supporting inquiry-based learning in physics, particularly in the context of parabolic motion experiments.